Replicating potato spindle tuber viroid RNA is accompanied by short RNA fragments that are characteristic of post-transcriptional gene silencing - Papaefthimiou, Ioannis (Oxford University Press, 2001)
The low molecular weight fraction of tomato plants inoculated with potato spindle tuber viroid (PSTVd) contains a population of short PSTVd-specific RNAs of either polarity. The main constituents were RNAs of 22 and 23 nt representing different domains of the viroid genome. The occurrence of such distinct RNA species indicated that the nuclear replicating PSTVd RNA induces post-transcriptional gene silencing. The short RNAs were slightly more abundant at 30 days post-inoculation than at later stages and were present in plants infected with a mild, severe or lethal isolate of PSTVd. There was no apparent correlation between the quantity of small PSTVd-specific RNAs and the degree of virulence of the viroid isolate.